Students' Conceptual Understanding of Measurement Topic in Development of Digital Teaching Materials Based on the Cognitive Conflict Learning Model Using Kodular - Yessi Ramadhani; Wahyuni Satria Dewi; Fatni Mufit; Emiliannur Emiliannur (Jurnal Penelitian Pembelajaran Fisika, 2025)
Physics learning often challenges students due to the abstract nature of the concepts. Effective teaching methods are needed to improve students' understanding, one of which is the cognitive conflict learning model. This model helps address misconceptions and clarify difficult concepts. This study aims to analyze students' conceptual understanding in developing digital teaching materials using the cognitive conflict model with Kodular on the topic of measurement at SMA Negeri 13 Padang. A descriptive qualitative approach was used, consisting of four stages: distributing questionnaires to physics teachers, developing research instruments, collecting data through observation and the Three-Tier Diagnostic Test, and analyzing students' responses. The subjects were 36 tenth-grade students in phase E3. The results show that 73.87% of students have misconceptions, 22.78% lack a solid understanding, and only 3.35% demonstrate correct understanding. These findings highlight the need for more effective learning models to enhance students' conceptual understanding.